2014
DOI: 10.1093/jnci/dju270
|View full text |Cite
|
Sign up to set email alerts
|

Lineages of Oncogenic Human Papillomavirus Types Other Than Type 16 and 18 and Risk for Cervical Intraepithelial Neoplasia

Abstract: These findings suggest that for a given HPV type, intratypic nucleotide changes may alter phenotypic traits that affect the probability of neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 53 publications
5
52
0
Order By: Relevance
“…The present study is an extension of our previous observation that risks of CIN2/3 differed significantly by variant lineages of HPV types 31/33/45/56/58 . In this study of women with these HPV types newly detected during a 2‐year follow‐up, we found that infections with HR, compared with non‐HR, variants tended to be marginally more likely to become negative.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The present study is an extension of our previous observation that risks of CIN2/3 differed significantly by variant lineages of HPV types 31/33/45/56/58 . In this study of women with these HPV types newly detected during a 2‐year follow‐up, we found that infections with HR, compared with non‐HR, variants tended to be marginally more likely to become negative.…”
Section: Discussionsupporting
confidence: 68%
“…Despite a high degree of DNA sequence homology between HPV variants, some differ in their group phenotypic traits. We previously analyzed intratypic diversity of oncogenic types other than HPV16 and HPV18, showing that risks of cervical precancer, defined clinically as cervical intraepithelial neoplasia Grades 2–3 (CIN2/3) differed significantly by variant lineages of five types ( i.e ., HPV31, HPV33, HPV45, HPV56 and HPV58) . We have postulated that genetic changes accumulated in the long‐term viral evolution may have altered certain biologic properties of the virus which are responsible for the observed risk difference.…”
mentioning
confidence: 99%
“…Methods for PCR sequencing and analysis were described previously. 13, 14 If ≥1 nucleotide alteration was detected among type-specific isolates in different samples from one woman, they were considered to be different variants. In analyses, paired samples with different variants were considered discordant; if variant results were unavailable, paired samples positive for the same HPV type were assumed to be concordant.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-genome sequence analysis of HPV45 strains has led to the delineation of distinct variant lineages (A and B) and sublineages (A1, A2, A3, B1, and B2) (3,6,7), with the possibility of a lineage C suggested from subgenomic sequences (8). Although firm data on their contribution to the risk of cervical disease progression are lacking, in part due to the low relative prevalences of individual lineages and sublineages in the population, current evidence does support some lineage-specific bias such that sublineage variant B2 (and possibly A3) appears to be overrepresented in patients with high-grade disease compared to controls (8)(9)(10). There may also be some geographical bias to the distribution of HPV45 sublineages (9).…”
Section: ϫ8mentioning
confidence: 99%